2011
DOI: 10.3109/17482968.2011.574141
|View full text |Cite
|
Sign up to set email alerts
|

Urinary disorders in amyotrophic lateral sclerosis subjects

Abstract: Amyotrophic lateral sclerosis (ALS) related disorders are considered to be uncommon. We hypothesize that urinary dysfunction may occur in ALS patients in the context of spasticity of pelvic floor musculature. We recorded data on 54 subjects with ALS. All subjects were evaluated with ALSFRS and M-Ashworth Scale for lower limbs. Bladder scan procedure was performed to asses post void residual (PVR) in all subjects. Forty-one percent of subjects were symptomatic for urinary disorders and 35% of subjects had a PVR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…Dysuria and urinary catheter insertion are often encountered in advanced ALS patients. While there have been no reports examining voiding dysfunction in patients with TIV, patients with early stages of ALS often exhibit an overactive or hypoactive bladder . Voiding difficulty is partly attributed to weakness of the pelvic or abdominal wall muscles, but a neurogenic mechanism may contribute to bladder dysfunction with disease progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysuria and urinary catheter insertion are often encountered in advanced ALS patients. While there have been no reports examining voiding dysfunction in patients with TIV, patients with early stages of ALS often exhibit an overactive or hypoactive bladder . Voiding difficulty is partly attributed to weakness of the pelvic or abdominal wall muscles, but a neurogenic mechanism may contribute to bladder dysfunction with disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…While there have been no reports examining voiding dysfunction in patients with TIV, patients with early stages of ALS often exhibit an overactive or hypoactive bladder. [47][48][49] Voiding difficulty is partly attributed to weakness of the pelvic or abdominal wall muscles, but a neurogenic mechanism may contribute to bladder dysfunction with disease progression. Some patients with superoxide dismutase-1 gene variants have a neurogenic or atonic bladder.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lopes de Carvalho et al reported a prevalence of urinary symptoms of 40% in ALS patients according to El Escorial criteria, but they do not clarify whether PLS phenotype was included or not, nor which questionnaires and methodology were used to asses LUTS. 5 Both voiding (''incomplete emptying'') and storage (''nocturia,'' ''frequency'') symptoms were frequently found (24% and 22%, respectively) but UI was seldom reported (5.5%). However, a comparison to normal population or a measure of the severity of those urinary symptoms were lacking.…”
Section: Discussionmentioning
confidence: 99%
“…These symptoms are the result of the spreading of the disease to different neuronal networks other than pyramidal tracts and supports the view of ALS as a multisystem disorder . Consequently, lower urinary tract symptoms (LUTS) have been reported in ALS patients although its prevalence differs widely between studies ranging from 4% to 40% . Moreover, underlying causes and pathophysiologic mechanisms have not been properly studied.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation